Improving Work Welfare Through Workload Analysis of Wreda Officers PPOS GBKP Sukamakmur Deliserdang - Eka; MR Tuapattinaja, Josetta; Fauzia, Rahma; Lestari Sitepu, Yuni (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Caregivers are people who assist others in need. Caregivers at the Prosperous Parents Service Foundation (YAPOS) consist of caregivers, cooks, and general workers who double as cleaning workers. All caregivers interact directly with YAPOS residents, namely the elderly, who are cared for by their families. The workload and the division of shifts, which only consist of two changes, certainly burden the caregivers. Excessive workload on weaving can cause high work stress. The workload must be measured immediately to provide input for YAPOS leaders to provide interventions on increasing or decreasing the number of caregivers to achieve a practical and ideal workload. This workload measurement can be carried out objectively so that it becomes the basis for assigning tasks and responsibilities in the future. The measure will also result in valuable work time and the amount of workload felt by the caregivers.